Earthworm abundance and availability does not influence the reproductive decisions of black‐tailed godwits in an agricultural grassland. Issue 1 (19th January 2022) - Verhoeven, Mo A.; McBride, Alice D.; Hooijmeijer, Jos C.E.W.; Piersma, Theunis; Senner, Nathan R.
Abstract: Maintaining the biodiversity of agricultural ecosystems has become a global imperative. Across Europe, species that occupy agricultural grasslands, such as black‐tailed godwits ( Limosa limosa limosa ), have undergone steep population declines. In this context, there is a significant need to both determine the root causes of these declines and identify actions that will promote biodiversity while supporting the livelihoods of farmers. Food availability, and specifically earthworm abundance (Lumbricidae), during the pre‐breeding period has often been suggested as a potential driver of godwit population declines. Previous studies have recommended increasing the application of nitrogen to agricultural grasslands to enhance earthworm populations and aid agricultural production. Here we test whether food availability during the pre‐breeding period affects when and where godwits breed. Using large‐scale surveys of food availability, a long‐term mark‐recapture study, focal observations of foraging female godwits, and tracking devices that monitored godwit movements, we found little evidence of a relationship between earthworm abundance and the timing of godwit reproductive efforts or the density of breeding godwits. Furthermore, we found that the soils of intensively managed agricultural grasslands may frequently be too dry for godwits to forage for those earthworms that are present. The increased application of nitrogen to agricultural grasslands will therefore likely have no positive effect on godwit populations. Instead, management efforts should focus on increasing the botanical diversity of agricultural grasslands, facilitating conditions that prevent hardening soils, and reducing the populations of generalist predators. Abstract : Earthworm abundance does not influence the reproductive decisions of black‐tailed godwits in Dutch agricultural grasslands. Instead of trying to help godwits by increasing earthworm numbers, we should focus on improving conditions such as water levels.